Flail chest and mediastinitis with total sternal loss post pediatric heart surgery. Reconstruction technique and case report - Palma-Ortecho, Luis J. (2023)
We present the case of a two-year-old girl, with a history of pulmonary banding surgery who underwent a chest wall stabilization technique with titanium rods and muscle flaps coverage, due to post-surgical mediastinitis associated with total sternal loss after ventricular septal defect closure surgery, debanding, and pulmonary artery plasty. The patient had a favorable postsurgical evolution.